2008
DOI: 10.1128/aem.00441-08
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial Denitrifier Community Abundance over Time in an Agricultural Field and Their Relationship with Denitrification Activity

Abstract: This study measured total bacterial and denitrifier community abundances over time in an agricultural soil cropped to potatoes (Solanum tuberosum L.) by using quantitative PCR. Samples were collected on 10 dates from spring to autumn and from three spatial locations: in the potato "hill" between plants (H), close to the plant (H p ), and in the "furrow" (F). The denitrification rates, N 2 O emissions, and environmental parameters were also measured. Changes in denitrifier abundance over time and spatial locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
7
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 35 publications
10
92
7
3
Order By: Relevance
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
“…As assessed by quantitative PCR methods, the abundance of denitrifying bacteria was reported to be 10 5 to 10 9 g −1 upland soil (9,14,16,17,37) and 10 6 to 10 7 g −1 paddy soil (45,46). These counts appear to be lower than the results obtained in the present study by direct in situ PCR.…”
contrasting
confidence: 56%
“…Although the present study was useful in understanding the effect of NO 3 Ϫ on cnorB gene expression in P. mandelii culture with or without NO 3 Ϫ addition, the effect of different NO 3 Ϫ concentrations, including intermediate NO 3 Ϫ concentrations on cnorB, nirS, and nosZ denitrification genes, was not addressed. Many denitrification studies use the acetylene inhibition method to measure short-term denitrification activity in soil (6,11,15,17,18,20,23) and pure cultures (3,19,25). Acetylene blocks the action of nitrous oxide reductase enzyme, thereby inhibiting the reduction of N 2 O to N 2 (3,12,25).…”
mentioning
confidence: 99%